INNOVATION OF LEARNING MEDIA WITH SMART TV TO INCREASE STUDENTS' INTEREST IN LEARNING - Hidayati, Nur; Manshur, Umar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to evaluate the impact of using Smart TV as a learning medium at Madrasah Aliyah Darul Hasan on the quality of the teaching and learning process. Using a qualitative approach with descriptive methods, data were collected through observation, interviews, and documentation. The study results indicate that Smart TV successfully creates more engaging, interactive, and relevant learning. Visual features such as videos, animations, and graphics help students understand complex materials and increase enthusiasm, participation, and involvement in class discussions. From the teacher's perspective, using Smart TV allows for more varied and efficient delivery of materials. Features such as digital quizzes, simulations, and educational applications support collaborative and dynamic learning. This implementation also successfully increases students' learning motivation, which positively impacts their learning outcomes. However, this study identified several challenges, including the need for teacher training to optimize technology and regular device maintenance. Support from the principal and the school is a significant factor in the success of this innovation, especially in areas with limited access to technology. The conclusion of this study shows that the implementation of Smart TV significantly contributes to improving the quality of education at Madrasah Aliyah Darul Hasan. In the future, closer integration with the curriculum, ongoing teacher training, and student mentoring are needed to maximize the potential of this technology. With consistent support, the use of Smart TV has the potential to provide a positive long-term impact on the world of education.